INSTAGRAM SEBAGAI SOCIAL MEDIA MARKETING DALAM MEMBANGUN BRAND AWARENESS FAKULTAS EKONOMI DAN BISNIS ISLAM - Oktaria Ardika Putri (Istithmar: Jurnal Studi Ekonomi Syariah, 2019)
Instagram is a social media application that is currently very popular in the community, especially among artist, politicians, and business people. Companies or advanced business must quicly adapt to the advancement of information technology in the form of social media as a marketing tool. Instagram social media also necessary to developing educational institutions. One of the educational institution that ae currently developing is the newly established Faculty of Economics and Business Islam (FEBI) at the Kediri State Islamic Institute (IAIN Kediri). This writing aims to examine the importance of Instagram as social media marketing to building FEBI IAIN Kediri Brand Awareness. Instagram social media is considered more effectives to embrace students and the community, so it is expected to facilitate marketing and communication between FEBI IAIN Kediri with the students or other agencies. The method of this reasearch is a qualitative analysis which reference libraries are used as a basis.